Counseling of Balanced Nutrition as an Effort to Increase Mother's Knowledge on Preventing Malnutrition (Case Study in Mojo Village, Kalitidu District, Bojonegoro Regency) - Christin Panjaitan; Erni Astutik (Media Gizi Kesmas, 2021)
ABSTRACTBackground: Malnutrition is a nutritional problem in children under five that still occurs today, including in Indonesia. East Java is one of the province that contributes quite a lot of malnourished children under five. Long-term malnutrition will impact the quality of human resources.Objective: To analyze the relationship between providing balanced nutrition counseling with the increase of mother's knowledge to prevent malnutrition.Methods: The method used in this study is Quasi Experiment with one group pre-test and post-test design. The sampling technique is the total sampling method, the sample are all mothers who have children under five in Mojo Village, Kalitidu District, Bojonegoro Regency as many as 42 people. Mojo Village was selectedpurposively. The dependent T-test was used to measure the differences of the mother's knowledge level before and after the education being given. The response rate of this study is 71.4%.Results: The results showed that at the beginning of the session before the counseling being given, 50% of mothers had good knowledge, sufficient knowledge 40%, and lacked knowledge 10%. After the counseling was carried out, 60% of mothers had good knowledge and sufficient knowledge 40%. The mean score before counseling was 67.33 ± 15.30 and after counseling, it changed to 72.00 ± 9.90 (P <0.05).Conclusion: The provision of balanced nutrition counseling in Mojo Village is significantly associated with the increase of mother's knowledge to prevent malnutrition. The Nutritionist in Puskesmas and Posyandu cadres have an important role in providing nutrition education to mothers to prevent malnutrition.Keywords: balanced nutrition, counseling, knowledge, malnutrition